PENGARUH HARGA, KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUASAN KONSUMEN SERTA IMPLIKASINYA PADA KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI - Maghfiroh, Kuni (Business Management Analysis Journal (BMAJ), 2019)
This study aims to analyze the effect of price, product quality, and word of mouth on consumer satisfaction and its impulse on the decision of purchasing a Xiaomi smartphone at. Data collection using questioners. The sample consisted of 160 respondents taken by purposive sampling method. The results of this test indicate that  price has a negative and not significant effect on customer satisfaction,  product quality has a positive and significant effect on customer satisfaction, word of mouth has a positive and significant effect on customer satisfaction, the price has a negative and not significant effect on the purchase decision, product quality has a positive and significant effect on purchasing decisions,  word of mouth has a negative and not significant effect on purchasing decisions,  customer satisfaction has a positive and significant effect on purchasing decisions. The most dominant variable or one that has the most influence is consumer satisfaction and product quality.